Preservation of Local Culinary Tourism in Improving the Economy of Local Communities in Surabaya - Mau, Daniel Pandu; Mau, Yesarela Pandu; Wibowo, Otje Herman; Kurniansah, Rizal; Artana, I Wayan Arta; Ariawan, I Wayan Adi Putra (GREENOMIKA, 2024)
Traditional Indonesian cuisine, including that of Surabaya, plays an essential role in the cultural identity and heritage of the region. However, rapid globalization and modernization have led to declining interest in traditional foods, particularly among younger generations, who prefer fast food. This study aimed to analyze the role of culinary tourism in preserving and promoting traditional Surabaya cuisine, identify the challenges and strategies for its development to increase its appeal, and examine its contribution to the local economy. The research employed a qualitative descriptive approach with case studies, involving interviews with culinary entrepreneurs and tourists and observations at key culinary tourism destinations. The findings revealed that, although culinary tourism has the potential to support the preservation of traditional cuisine, the main challenges identified were ineffective promotion, insufficient supporting infrastructure, and a lack of interest among younger generations in continuing traditional culinary businesses. Therefore, collaborative efforts between the government, business owners, and local communities are needed to enhance promotion, quality, and the overall culinary tourism experience, which can positively impact the local economy through increased tourist visits and regional consumption.